Interaction of galactoglucomannan oligosaccharides with auxin involves changes in flavonoid accumulation - Kučerová, Danica (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.